The Missing Masters of 1 Peter - Maston, Jason (New Testament studies, 2025)
One of the intriguing features of the Petrine household code (1 Pet 2.18-3.7) is the lack of instructions to masters. A common view claims that there are no instructions because there were no Christian masters in the community. This view, however, is textually and historically unlikely. This essay, rather, considers how the instructions to enslaved persons and the lack of instructions to masters might have been heard from the perspective of a Christian master. The first part of the essay highlights some features of literature on household management and perceptions of enslaved persons’ moral competency. The essay then turns to 1 Peter to analyse the theological perspective of the household code and the description of enslaved persons. I propose that the author has intentionally ignored masters as part of his defining the house of God.